QUANTITATIVE ASSESSMENT OF POPULATIONS, SUBPOPULATIONS OF LYMPHOCYTES AND PHAGOCYTIC CELLS IN HIV-PATIENTS - N.V. Ilenko; T.A. Petrushanko; N.N. Ilenko (Ukrainian Medical Stomatological Academy, 2016)
The epidemiological situation in Ukraine on HIV / AIDS has become worse. That is why a profound and detailed study of all aspects of HIV infection is extremely important. In the course of our research we carried out a quantitative assessment of populations and subpopulations of lymphocytes and phagocytic cells in HIV-infected patients in relation to the characteristics of the dental status of these persons. There were examined 94 HIV-infected patients (58 women and 36 men) aged 20-49 years. They were at the dispensary in the Poltava Regional Centre of AIDS Control and Prevention. General clinical oral cavity examination was performed with definition of indexes CPE, OHI-S J.C.Green, J.R.Vermillion, РМА modified by Parma, PI by Ramfjord, CPI by Leus, test by Pisarev-Shiller, determination of iodine number by Svrakov, bleeding index by H.P.Muhlemann and floss and halimetria test. 93 patients conducted laboratory peripheral blood studies to determine the content of CD4-lymphocytes in the blood of HIV-patients using modular analyzer «FACSCalibur» (Biosciences, USA). Study of expression of cluster of differentiation CD4, CD3 and CD45 on lymphocytes plasmolemma used the medical records of patients with HIV status under terms that suggest their validity. The data was processed statistically. The increase in total number of lymphocytes was found in about 40% of patients. 44 people (46.81%) were diagnosed with AIDS-defining somatic diseases and tumors. It can be argued that the lymphocytosis in our patients is the result of reactive states that is the onset and progression of opportunistic infections. Lymphocytopenia in our patients is a deep decompensated symptom of HIV / AIDS. It is revealed that in one third of the surveyed there was a reduction in absolute content of T-lymphocytes in the peripheral blood. It is a sign of infection or immunodeficiency, inflammatory diseases, tumors, necrotic changes. Studies have identified a number of changes in the peripheral blood of HIV-patients which are typical for reactive states of the body associated with opportunistic infections and neoplastic processes in patients with HIV infection. It was found that the indicators of the index assessing the state of the oral cavity of HIV- patients are deteriorating with a decrease the number of lymphocytes, which are expressed on plasmolemma clusters of CD4 differentiation. A progression of inflammatory and degenerative changes in the periodontal complex with a reduction in CD4-lymphocytes persists as a reliable state. We have also studied phagocytic cells in peripheral blood. We found that more than half of HIV-infected individuals showed a reduced level of neutrophils. It is a poor prognostic sign in the development of a bacterial infection caused by endogenous opportunistic pathogens. In about 60% of the patients there were clear signs of monocytosis associated with subacute and chronic bacterial infections, parasitic infections and other reactive states against the background of HIV infection.